Analysis of cellular senescence-related genes in calcified aortic valve disease and the potential therapeutic role of β-Carotene - Yijing Tao; Chengjie Gao; Juan Wang; Qiyin Zhang; Zhisong Wang; Leng Han; Donglai Cao; Qianwen Yao (PLoS ONE, 2025)
Objective Calcific aortic valve disease (CAVD) is a progressive, age-related degenerative disease characterized by the accumulation of calcium deposits in the aortic valve. We aim to screen key genes associated with cellular senescence (CS) in CAVD. Methods The GSE12644 and GSE51472 datasets from the GEO database was utilized in this study, and differentially expressed genes (DEGs) were identified using the “limma” R package. CS-related DEGs (CS-DEGs) were determined through the CellAge database. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed on CS-DEGs. A protein–protein interaction (PPI) network was constructed using the STRING database. The cytoHubba plug-in in Cytoscape was used to identify hub genes. A noncoding-RNA-mRNA regulatory network was established. DSigDB database was used to to identify drugs potentially be useful for treating CAVD. Results A total of 16 CS-DEGs were identified. These genes were primarily associated with collagen metabolic process, collagen catabolic process and external side of plasma membrane. 10 hub genes were identified as regulators of cellular senescence in CAVD: LPAR1, PTPN6, CD28, ID1, MEIS2, FGFR3, KDR, MMP7, AR, HIF1A. The Noncoding RNA-mRNA regulatory network indicated that CS-DEGs may be regulated by noncoding RNAs. β-Carotene, a naturally occurring carotenoid with antioxidant properties, was identified potential therapeutic agents through interacting with MMP9, MEIS2, and CTSB. Conclusion This study provides insights into the key genes and pathways related to cellular senescence in CAVD (MMP9, MEIS2, and CTSB) and highlights the potential role of β-Carotene treatment of CAVD.